Metodika práce s třídním kolektivem v inkluzivní třídě se zaměřením na žáky se sluchovým postižením Metodická příručka - Bytešníková, Ilona (Masaryk University Press, 2020)
Title in English: Methodology of Classroom Management in Inclusive Classroom with a Focus on Pupils with Hearing Disability: Methodological Manual The methodology introduces the specific features of the educational process of a pupil with a hearing disability. The structure of the text reflects the systematic summary of various types of hearing impairment. It includes the specifics of the principles of right communication with pupils with hearing disability during individual and also teamwork, organization of the educational process methods and forms of the teaching, professional support during the lessons and diverse ideas concerning the activities with pupils with hearing disability and the collective of the classroom. The book comprises a chapter presenting outcomes of a research, which was administered in a chosen school educating a pupil with hearing disability. The text contains examples of successful practice.